Niełatwa archeologia klifów – przypadek stanowisk w Bagiczu - Chmiel-Chrzanowska, Marta (Folia Praehistorica Posnaniensia, 2019)
The following paper presents the problem of archaeological sites located on cliffs on the Southern Baltic Sea shore. This article discusses issues related to a necessity of solving the problem of this kind of research, related to methodological, as well as documentation and preservation standards based on preliminary results of the project conducted in Bagicz area (Ustronie Morskie commune). In this region four new structures were noted on a cliff surface. The key to understand the situation of archaeological sites located on a cliff areas is the knowledge of the processes related to their formation and activity. All of them have a huge impact for the state of preservation of the cliff, however they have various intensity level depending on the part of the Baltic Coast.